1964
DOI: 10.1071/sr9640083
|View full text |Cite
|
Sign up to set email alerts
|

Reactions between boron and clays

Abstract: Sorption of boron by Kent sand kaolinite, WilIalooka illite, and Marchagee montmorillonite in 0.01M CaCl2 is consistent with a mechanism described by the Langmuir equation, except that deviations occur at solution concentrations greater than about 10 �g B/ml. The quantity of boron adsorbed increases markedly with pH, and is rapid, reversible, and unaffected by the concentration of calcium chloride present. Complete desorption of surface boron, without significant solution of lattice boron, is achieved with 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
10

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 0 publications
3
48
0
10
Order By: Relevance
“…Hingston (1964) found that the treatment of illite with CaCO 3 at the rate of 2 % resulted in decreasing B sorption capacity at pH 7.5 and 8.3; however, addition of CaCO 3 at pH 9.5 did not significantly influence B sorption when compared to untreated illite at pH 8.5. Ichikuni and Kikuchi (1972) suggested that B sorption on CaCO 3 can likely occur through precipitation of low-solubility calcium borate, B replacement with carbon in CaCO 3 , and adsorption of B on CaCO 3 surfaces.…”
Section: Introductionmentioning
confidence: 88%
“…Hingston (1964) found that the treatment of illite with CaCO 3 at the rate of 2 % resulted in decreasing B sorption capacity at pH 7.5 and 8.3; however, addition of CaCO 3 at pH 9.5 did not significantly influence B sorption when compared to untreated illite at pH 8.5. Ichikuni and Kikuchi (1972) suggested that B sorption on CaCO 3 can likely occur through precipitation of low-solubility calcium borate, B replacement with carbon in CaCO 3 , and adsorption of B on CaCO 3 surfaces.…”
Section: Introductionmentioning
confidence: 88%
“…. In fact, kaolinite adsorbs B the least (Hingston, 1964;Fleet, 1965). Frederickson & Reynolds (1959) proposed that most of the B in the clay mineral fraction of sedimentary rocks is contained in the illite fraction.…”
Section: Soil Texture and Clay Mineralsmentioning
confidence: 99%
“…In early studies by Olson humus, values that were much higher than and Berger (1946), destruction of soil organic reported for B retention by clay minerals and matter by oxidation led to significant release whole soils (Hingston 1964; of B in plant-available form, and caused a O'Connor 1982;Evans 1987 x,x*Significant at P : 0.05 and P = 0.01, r$pectively. (Hatcher et al .…”
mentioning
confidence: 99%
“…Sposito (1984) has also emphasized the value of spectroscopic methods for examining adsorption mechanisms. NMR (Knoeck and Taylor 1969) and spectrophotometric (Wildes and Neales 1969) 7.5 and, for B concentrations from 0 to 0.7 mol m-3 (Hingston 1964 Evans (1987).…”
mentioning
confidence: 99%